2015
DOI: 10.3892/mmr.2015.4090
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the nasopharyngeal carcinoma primary tumor-associated gene interaction network

Abstract: The aim of the present study was to investigate the molecular mechanism of nasopharyngeal carcinoma (NPC) primary tumor development through the identification of key genes using bioinformatics approaches. Using the GSE53819 microarray dataset, acquired from the Gene Expression Omnibus database, differentially expressed genes (DEGs) were screened out between NPC primary tumor and control samples, followed by hierarchical clustering analysis. The Search Tool for the Retrieval of Interacting Genes database was ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Chen’s research based on two gene expression profiles (GSE12452 and GSE13597) identified 179 upregulated and 238 downregulated DEGs, including 10 hub genes for which authors supposed to be useful for facilitating the early diagnosis and curative treatment of NPC [18]. Similar studies take out by An and colleagues applied GSE53819 microarray dataset for bioinformatic analysis and revealed that EXO1, CENPF, ANLN, PBK, and C15ORF42 may be involved in the mechanism of NPC via modulating the cell cycle and nucleic acid metabolic processes [19]. But in the present study, except for the dataset GSE12452, another dataset GSE64634 was also acquired for the identification of DEGs; 10 upregulated and 142 downregulated were identified based on these two datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Chen’s research based on two gene expression profiles (GSE12452 and GSE13597) identified 179 upregulated and 238 downregulated DEGs, including 10 hub genes for which authors supposed to be useful for facilitating the early diagnosis and curative treatment of NPC [18]. Similar studies take out by An and colleagues applied GSE53819 microarray dataset for bioinformatic analysis and revealed that EXO1, CENPF, ANLN, PBK, and C15ORF42 may be involved in the mechanism of NPC via modulating the cell cycle and nucleic acid metabolic processes [19]. But in the present study, except for the dataset GSE12452, another dataset GSE64634 was also acquired for the identification of DEGs; 10 upregulated and 142 downregulated were identified based on these two datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Genes that were up-regulated/down-regulated in tumor vs. normal tissues and simultaneously down-regulated/up-regulated in tumor-CRT vs. tumor-non-CRT samples were regarded as potential CRT-sensitive genes. Then, two-way hierarchical clustering analysis was applied for these CRT-sensitive genes using the heatmap package [17].…”
Section: Methodsmentioning
confidence: 99%
“…An independent analysis of TCGA RNA-Seq data encompassing 12 cancer tissues has uncovered liver cancer-specific genes (Peng et al, 2015). Zhang et al (2015) have performed mutation analysis of LIHC, and Yang et al (2017) combined TCGA expression data and natural language processing techniques to identify cancer-specific markers.…”
Section: Introductionmentioning
confidence: 99%